Harnessing Nature's Vibrations - Boom, Bart Aron Robertus (My University, 2025)
This dissertation addresses the gap in understanding dynamical behaviors between biology and engineering by using two systems: 1) batoid swimming dynamics, 2) and water entry of diving birds. I address how shape and stiffness change the dynamical response of these two systems and analyze their combined effect. I combine the approaches of biology and engineering to gain an understanding of the mechanistic morphological optimization for dynamical functions. In my first chapter, I examine how the development of batoid bio-inspired robotics has been constrained by the limited foundational biological datasets available. By incorporating detailed morphological studies of a greater range of batoids, there is the possibility for improving performance of current robotics, and in turn they would allow biologists to use them to study batoid locomotion. In my second chapter, I found that batoids use the natural mode shapes of their fins to create more efficient swimming patterns and I was able to estimate the wavenumber from the first three mode shapes. I found that the relationship between the span- and chord-wise stiffness can change the direction of the traveling wave. In my third chapter, I found that diving bird necks use compliance to damp the impact of high forces generated during water entry. However, they do not use damping as would be expected, instead they use the water as an external damping mechanism to minimize vibration down the neck. By using a dynamical approach I was able to show that shape and impact speed are important for diving birds, and I showed that the shape batoids is the most important for generating undulatory patterns instead of the actuation that is classically though as the main factor. These findings would not have been possible with a quasi-static approach that most biological studies are limited to. Both examples show behaviors that use damping and morphology in complex ways that engineers can learn from. Biology shows how shape can drive a lot of behaviors, by changing the shape and stiffness we are able to tune mode shapes to create desired behaviors without needing large amounts of actuators and complex control systems. Nature is harnessing vibrations in a way engineers can learn from.
Thesis (Ph.D.)--University of Washington, 2025
Keywords: Batoid; Diving bird; Impact; Propulsion; Aerospace engineering; Biomechanics; Aeronautics and astronautics